Pharmaceutical chemistry. Section 1.3. Analysis of medicines of the antibiotic group: study and methodical guide for 4th year students of the specialty "Pharmacy, Industrial Pharmacy" - Shabelnik, K. P.; Derevianko, N. V.; Akopian, R. R.; Шабельник, Костянтин Петрович; Дерев'янко, Наталя Вікторівна; Акопян, Ріма Романосівна (Запорізький державний медико-фармацевтичний університет, 2023)
The study guide for students is compiled in accordance with the requirements of the Central Methodical Council of Zaporizhzhia State Medical and Pharmaceutical University. Published for the first time.